Prevalence of Tooth Wear among different age group of patients visiting Private Dental Hospital- A Retrospective study - FAREEN, H. FIRDUS; KUMAR. R, PRADEEP; SRI. RENGALAKSHMI (The journal of contemporary issues in business and government, 2020)
Tooth wear is generally defined as irreversible chronic loss of dental hard tissues caused by mechanical and/or chemical processes without the involvement of bacterial plaque. To some degree, tooth wear is physiological and age dependent. The aim of the study was to evaluate the prevalence of tooth wear among different age groups of patients visiting private dental hospital. Date of age, gender, type of tooth wear of patients were obtained from the records of the dental hospital.The data was analysed using SPSS software. Chi Square Test was performed to compare two proportions. The analysis was done for: age, gender and the type of tooth wear. The Prevalence rates of tooth wear in dental patients were calculated. The patients were ranged in the age group of 20- 30 years, 31-40 years, 41-50 years and above 50 years. The overall prevalence rate for attrition was seen most commonly in the age group of 31-40 years (43.86%) with higher incidence among males. Patients in the age group of 31-40 years (56.41%) showed highest prevalence for abrasion with higher incidence among males and the prevalence rate for erosion was most commonly observed in the age group of patients 31-40 years (26.91%) with higher incidence among males which was found to be statistically significant (P<0.05). The study may help in planning patient’s diagnostic protocol and management strategy among dentists.